Safety of the use of a microtracer with the feed additive consisting of chromium propionate (KemTRACE™ chromium) for all growing poultry species - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract In the context of the FEEDAP opinion on the safety and efficacy of a feed additive consisting of chromium propionate (KemTRACE™ Chromium) of 18 March 2021, the EU Reference Laboratory for feed additives (EURL) was not in a position to recommend the method: proposed by the applicant for official control for the quantification of the organic chromium content in premixtures and feedingstuffs. The applicant subsequently proposed a new method of analyses, incorporating a tracer in the composition of a premix, which has been evaluated by EURL and recommended as official method for the quantification of the organic chromium content in premixtures and feedingstuffs. In view of the above, the Commission asked EFSA to issue a new opinion on the safety and efficacy of chromium proprionate (KemTRACE™ Chromium) as feed additive for all growing poultry species including the newly submitted information by the applicant that involves the use of the microtracer. The present opinion is limited to the assessment of the new information submitted by the applicant in support of safety of the proposed use of the microtracer in the composition of the premix. The FEEDAP Panel concluded that the use of the microtracer in the premixture, at the proposed level of use, does not present a risk for the target species and the consumer. The microtracer should be considered a dermal and respiratory sensitiser. Therefore, any exposure of users to the microtracer via skin or the respiratory tract is considered a risk. The use of the microtracer at proposed conditions of use is safe for the terrestrial environmental compartment, but no conclusion can be made for the groundwater. The addition of the microtracer in the premix/feedingstuffs is not expected to have any impact on the efficacy of the additive, and therefore, the previous conclusion on the efficacy is still valid.